Straightforward and controllable synthesis of heteroatom-doped carbon dots and nanoporous carbons for surface-confined energy and chemical storage - Park, Sul Ki; Lee, Hyunjoo; Choi, Min Sung; Suh, Dong Hoon; Nakhanivej, Puritut; Park, Ho Seok (Elsevier BV, 2018)
The valorization of waste is of prime importance for sustainable chemistry and replacement of fossil fuel-derived counterparts. However, existing synthetic methods are critically hampered by complicated and uncontrollable chemistry arising from heterogeneous sources. Herein, we demonstrate a separation-free, straightforward, and controllable chemical approach for the valorization of lignocellulosic biomass by conversion to heteroatom-doped and undoped carbon dots (CDs) and nanoporous carbons (CNs) via a novel mechanism. The incorporation of heteroatoms such as phosphorus (P), sulfur (S), and nitrogen (N) into the CDs and steam-activated CNs (aCNs) leads to changes in the electronic and surface properties, and affords morphological control based on the doping agents, for application to CO2 capture and supercapacitors. Controlling the chemical composition and structure of the CDs results in shifts and variations in the splittings of the PL peaks and fluorescence wavelength owing to the distinct optoelectronic features. The P, N, and S-doped aCNs (P-aCN, S-aCN, and N-aCN) have robust honeycomb, entirely exfoliated reed-like, and hollow isolated reed-like structures, respectively, with unique hierarchical porosity. N-aCN exhibits the highest CO2 capacity and regeneration capability owing to the existence of basic N-containing groups and the associated structural integrity. In terms of the supercapacitive performance, P-aCN achieves the highest capacitance owing to the pseudocapacitance of the (PO)-O-= bonds, whereas S-aCN leads to the best rate and cyclic capabilities owing to the unique porous structure and S-containing group. These distinctive energy and chemical storage behaviors of the CNs highlight the importance of controlling hierarchical structure and heteroatoms for improved ultracapacitive performance.